Technology engineering and management in aviation : advancements and discoveries - Abu-Taieh, Evon M. O.; El-Sheikh, Asim A, 1956-; Jafari, Mostafa, 1956- (Information Science Reference, 2012)
"This book details the essential new developments in technology and management in the aviation industry, specifically important advances in navigation, air traffic control, and environmental impact"--Provided by publisher